PENGAMBANGAN MEDIA POP UP BOOK UNTUK PENGENALAN PROFESI ANAK USIA 5-6 TAHUN DI TK ISLAM BAKTI 53 KOTO SALAK - Atina, Mia; Agus Saputra; Eka Filahanasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The introduction of professions to children helps children recognize professions that are around, develop thinking skills, and help children prepare for their future. The introduction of professions can be done using Pop Up Book media because of its unique and interesting shape when opened. The type of research is development research using the ADDIE development model.. Data collection used in this research is observation and questionnaire (questionnaire). The results of this study are based on validity tests, practicality tests and effectiveness tests. The results of the media validator analysis obtained a score of 100% with a very valid category, the material expert scored 94% with a very valid category, and the linguist validator obtained 89% with a very valid category. Practicality test with 1 teacher scored 88% with a very practical category. effectiveness test tested 15 children with a score of 93% with a practical category with an average achievement in the emerging category. Thus pop up book media for the introduction of professions is effective and can be used by teachers and children in Bakti 53 Koto Salak Islamic Kindergarten, Dharmasraya Regency.